Analisis Gaya Kepemimpinan Path Goal (Studi pada Karyawan di UMKM Sekka Shoes N Care Kecamatan Cimahi) - Rissalam Akmalu R; Moh Ramdani Hasbi; Mulani Nuryanti; Lidya Fauziyah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of leadership styles on employee performance at Sekka Shoes n Care MSME using the Path-Goal theory perspective. The research method employed is descriptive qualitative, with data collection techniques involving observation and in-depth interviews with the business owner and four employees (admin, courier, and technicians). The results indicate that the owner applies a situational combination of directive, supportive, and participative leadership styles. The directive style is primarily used for technical instructions on handling difficult materials. The supportive style is proven to increase employee loyalty through a personal approach and empathy toward field constraints. Meanwhile, the participative style encourages technical innovation derived from employee suggestions. Overall, the owner's leadership flexibility fosters a high sense of responsibility and improves the quality of employee performance at Sekka Shoes n Care.